Therapeutics from Cyanobacteria: A Review of Cyanobacteria-Derived Compounds as Anti-cancer Drug Leads - Wijewickrama, Menuja; Greene, Anthony; Cock, Ian (Pharmacognosy Reviews)
Cancer is a group of illness that collectively are the second highest cause of death globally after cardiac disease. They can also affect the social, psychological, physical and economic well-being of individuals, families and societies. Novel drug discovery for new cancer chemotherapeutics is a lengthy, complex, and costly process. Cancer drugs that are currently in clinical use have several drawbacks, including serious undesirable side-effects and the development of resistance to anticancer drugs. Thus, the development of novel effective and low toxicity cancer drugs is a priority for medical science. In recent decades, natural products-derived cancer drug discovery has become a promising avenue for drug development and an increasing number of studies have been published. Cyanobacteria have potential as a source for novel drug discovery. Cyanobacterial bioactive metabolites have a large diversity of chemical structures, modes of action and therapeutic targets. Multiple cyanobacteria-derived compounds have successfully reached clinical trials, and some have already been approved by regulatory authorities including the FDA as anticancer drugs. This review highlights the therapeutic potential of cyanobacteria in cancer drug discovery and summarizes the cyanobacterial compounds already used as cancer chemotherapies. The review aims to highlight cyanobacteria as sources of potential new drugs and focus future research on this field.
Keywords: Cyanobacteria; Bioactive compounds; Drug discovery; Anti-cancer compounds; Apoptosis; Clinical trials